2020
DOI: 10.1016/j.ymgmr.2019.100553
|View full text |Cite
|
Sign up to set email alerts
|

An incidental finding in newborn screening leading to the diagnosis of a patient with ECHS1 mutations

Abstract: Short-chain enoyl-CoA hydratase (ECHS1) is a mitochondrial beta-oxidation enzyme involved in the metabolism of acyl-CoA fatty acid esters, as well as in valine metabolism. ECHS1 deficiency has multiple manifestations, including Leigh syndrome early at birth or in childhood with poor prognosis, to cutis laxa, exercise-induced dystonia and congenital lactic acidosis.Here we describe the case of a newborn with mutations in ECHS1 that caught our attention after the incidental finding of 3-hydroxy-butyryl\3-hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
(45 reference statements)
0
16
0
1
Order By: Relevance
“…P12 died at 5 months from LS and respiratory infection. 23 The severe clinical deterioration by the time of genetic confirmation precluded any therapeutic intervention in this patient.…”
Section: Radiological and Genetic Features Of Patients With Sceh And Hibch Deficiencymentioning
confidence: 95%
“…P12 died at 5 months from LS and respiratory infection. 23 The severe clinical deterioration by the time of genetic confirmation precluded any therapeutic intervention in this patient.…”
Section: Radiological and Genetic Features Of Patients With Sceh And Hibch Deficiencymentioning
confidence: 95%
“…Early identification of this condition and initiation of treatment are crucial in order to avoid potentially devastating and irreversible neurological damage [ 7 ]. Even if the disease detected has no treatment available, early detection would allow for adequate genetic counseling [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, intermediate and mild cases usually have normal laboratory values. A review of the literature 1‐4,6‐29 revealed 67 patients with most suffering the early onset presentation. Average age at death was 28.0 + 43.8 months (range 16 h to 156 months) for 27 early onset patients (age <12 months) for whom age at death was reported.…”
Section: Introductionmentioning
confidence: 99%